Influence of biochar and microorganism co-application on stabilization of cadmium (Cd) and improved maize growth in Cd-contaminated soil - Haider, Fasih Ullah; Farooq, Muhammad; Naveed, Muhammad; Cheema, Sardar Alam; Ain, Noor ul; Salim, Muhammad Arslan; Liqun, Cai; Mustafa, Adnan (Frontiers in Plant Science, 2022)
Cadmium (Cd) toxicity and its potential remediation strategies have been widely used for improving crop production for last the few years. Yet, the synergistic effects of biochar and microorganisms on the adsorption of cadmium (Cd) and maize plant physiology remained unclear. Therefore, this experiment was conducted to evaluate the combined effects of biochar (BC) pyrolyzed from (maize-straw, cow-manure, and poultry-manure, and microorganisms [Trichoderma harzianum (fungus) and Bacillus subtilis (bacteria)], on plant nutrient uptake under various Cd-stress levels (0, 10, and 30 ppm). The highest level of Cd stress (30 ppm) caused the highest reduction in plant dry biomass, intercellular CO2, SPAD value, transpiration rate, water use efficiency, stomatal conductance, and photosynthesis rate by 27.06, 22.36, 34.50, 40.45, 20.66, 29.07 and 22.41%, respectively than control Cd0 (0 ppm). Sole application of BC and microorganisms significantly improved plant growth, intercellular CO2, SPAD value, transpiration rate, water use efficiency, stomatal conductance, and photosynthesis rate and caused a significant reduction in root and shoot Cd. However, the co-application of BC and microorganisms was more effective than the sole applications. In this regard, the highest improvement in plant growth and carbon assimilation and highest reduction in root and shoot Cd was recorded from co-application of cow-manure and combined inoculation of Trichoderma harzianum (fungus) + Bacillus subtilis (bacteria) was the most effective in improving maize growth and restricting the Cd uptake of plant grown in Cd-polluted soils. However, due to the aging factor and biochar leaching alkalinity, the effectiveness of biochar in removing Cd may diminish over time, necessitating long-term experiments to improve understanding of biochar and microbial efficiency for specific bioremediation aims.